Performance Evaluation of Non Orthogonal Multiple Access (NOMA) with digital modulation schemes (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Non Orthogonal Multiple Access (NOMA) isnew significant research area, as it gives novel idea ofmultiplexing the communication channels on the samefrequency and time slot , which can present revolutionaryoutcomes.The general idea of (NOMA) is based on usingSuccessive Interface Cancelling (SIC) , where each user ofthe channel is distinguished by its unique power level, andthen all the users are modulated/demodulated in certainorder.In this study, many experiments are run to examineNOMA with digital modulation schemes, such as ASK, PSK,FSK, QPSK, and 8 QAM. MATLAB codes are built toperform each experiment.According to the performed simulation, 8-QAM has thelowest Bit Error Rate (BER).